2020
DOI: 10.35371/aoem.2020.32.e19
|View full text |Cite
|
Sign up to set email alerts
|

The association between mercury concentrations and lipid profiles in the Korean National Environmental Health Survey (KoNEHS) cycle 3

Abstract: Background: High concentrations of mercury intake from seafood are known to cause various side effects in humans, including on the nervous system. Various studies have reported the effects of mercury concentrations in humans; however, the association between dyslipidemia, a cardiovascular disease risk factor, and mercury remains controversial. Therefore, this study aimed to investigate the association between mercury accumulation and cholesterol concentrations in a Korean population. Methods: We analyzed data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Furthermore, a study using the KoNEHS observed that BHg concentrations are significantly higher in the hyperlipidemia group (4.03 and 2.83 μg/L for male and female) than that in the non-hyperlipidemia group (3.48 and 2.69 μg/L of male and female), and individuals with higher BHg concentrations have a 11% higher risk of hyperlipidemia [ 50 ]. Significant increases in TC, HDL-C, and LDL-C levels are reported with increasing BHg concentrations in Korean adults, based on the KoNEHS [ 40 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study using the KoNEHS observed that BHg concentrations are significantly higher in the hyperlipidemia group (4.03 and 2.83 μg/L for male and female) than that in the non-hyperlipidemia group (3.48 and 2.69 μg/L of male and female), and individuals with higher BHg concentrations have a 11% higher risk of hyperlipidemia [ 50 ]. Significant increases in TC, HDL-C, and LDL-C levels are reported with increasing BHg concentrations in Korean adults, based on the KoNEHS [ 40 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDL-C was calculated as TC−HDL(C)−[TG/5] using Friedewald’s formula [ 38 ]. Owing to a limitation of the formula, TG values greater than 400 mg/dL were treated as missing values [ 39 , 40 ]. This is because TG levels above 400 mg/dL may be underestimated, owing to a decrease in the TC:TG ratio of very low-density lipoprotein cholesterol (VLDL-C) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Blood liver enzyme levels were measured in the KoNEHS by analyzing the serum concentrations of ALT and AST at a wavelength of 340 nm using a colorimetry (Colorimetry, Modified IFCC UV method, ADVIA 1800, Siemens, Munich, Germany) [ 31 ]. Abnormal cut-off points were defined as 35.0 IU/L or more for ALT and 40.0 IU/L or more for AST.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure of 57 workers to As showed that there is an increased level of the lipoprotein (a) (LP(a)), a ratio of apolipoprotein-B (Apo-B)/apolipoprotein-A1 (Apo-A1) and Apo-B level and a decreased level of Apo-A1, indicative of high-risk of heart diseases [ 36 ]. The exposure to Hg workers that experienced from Korean National Environmental Health Survey cycle 3 in 3228 samples indicated an increase in TC, TG, LDL, and VLDL [ 37 ]. Exposure to Pb of battery workers in Lucknow city (India) saw increased TC/HDL-C and LDL/HDL ratios [ 38 ].…”
Section: Epidemiological Evidence Of Lipid Alterations After Exposure...mentioning
confidence: 99%